2012
DOI: 10.1186/1471-2164-13-504
|View full text |Cite
|
Sign up to set email alerts
|

Intronic RNAs constitute the major fraction of the non-coding RNA in mammalian cells

Abstract: BackgroundThe function of RNA from the non-coding (the so called “dark matter”) regions of the genome has been a subject of considerable recent debate. Perhaps the most controversy is regarding the function of RNAs found in introns of annotated transcripts, where most of the reads that map outside of exons are usually found. However, it has been reported that the levels of RNA in introns are minor relative to those of the corresponding exons, and that changes in the levels of intronic RNAs correlate tightly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(98 citation statements)
references
References 55 publications
(76 reference statements)
4
91
0
2
Order By: Relevance
“…Second, we have focused only on the reference transcripts and have not yet explored individual isoforms. Future studies could include detection of novel transcripts and differential analysis of the splicing variants and their isoforms (32)(33)(34) by increasing the sequencing read depth. Third, we have omitted ASE filtering in the analysis of proportions of fetal-and maternal-derived transcripts for the early pregnancy samples, because the chorionic villi and amniotic fluid had been exhausted for the genotyping analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we have focused only on the reference transcripts and have not yet explored individual isoforms. Future studies could include detection of novel transcripts and differential analysis of the splicing variants and their isoforms (32)(33)(34) by increasing the sequencing read depth. Third, we have omitted ASE filtering in the analysis of proportions of fetal-and maternal-derived transcripts for the early pregnancy samples, because the chorionic villi and amniotic fluid had been exhausted for the genotyping analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms for expression regulation of ncRNA genes suggest that some expression regulation of ncRNA genes depend on gene locations in genomic DNA sequences. Such researches for intronic ncRNA genes have shown that many ncRNA genes are located in intronic regions [18][19][20][21]. Therefore, we should classify ncRNA genes based on gene locations in genomic sequences.…”
Section: Page 2 Of 11mentioning
confidence: 99%
“…With more and more genes being identified and annotated, some gene-related issues [6] are being studied, some of which are as follows: the identification of alternative splicing sites that determine the loci of introns and exons [155,156]; novel protein-coding prediction, which aims to find novel protein coding regions [136]; ncRNA prediction, which focuses on long or small regulatory ncRNA [157][158][159] in so-called intergenic regions; and finding other functionally non-genic elements that mainly exist in non-genic areas and play an active role in regulating gene expression [160]. Furthermore, some important biological signals are considered to be relevant to gene structures, such as polymorphism, CpG island, and Methylation, etc.…”
Section: Relevant Issuesmentioning
confidence: 99%